2020
DOI: 10.1016/j.xfre.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Transfers of lower quality embryos based on morphological appearance result in appreciable live birth rates: a Canadian center’s experience

Abstract: Objective: To determine the reproductive outcomes resulting from transfer of lower-grade blastocysts to support the practice of cryopreserving and transferring lower-grade embryos. Design: Retrospective chart review. Setting: Single infertility center. Patient(s): Women who have undergone a fresh (n ¼ 570) or frozen (n ¼ 885) transfer of a single blastocyst embryo between December 2013 and December 2018. Intervention(s): None. Main Outcome Measure(s): The primary outcome was live birth rate. The secondary outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Furthermore, embryos of insufficient morphologic grade may be discarded before biopsy, lowering the total number of embryos available for transfer. Data suggest that embryos of lower morphologic grade do have appreciable live birth rates and should be considered for transfer (14). In a recent review, Kemper et al (15) evaluated randomized controlled trials comparing IVF with and without PGT-A and found that only 2 trials examined the CLBRs per started cycle.…”
mentioning
confidence: 99%
“…Furthermore, embryos of insufficient morphologic grade may be discarded before biopsy, lowering the total number of embryos available for transfer. Data suggest that embryos of lower morphologic grade do have appreciable live birth rates and should be considered for transfer (14). In a recent review, Kemper et al (15) evaluated randomized controlled trials comparing IVF with and without PGT-A and found that only 2 trials examined the CLBRs per started cycle.…”
mentioning
confidence: 99%
“…Although a similar cancellation rate was observed between the two groups before the first transfer cycle, the oocyte utilisation rate in the conventional IVF/ICSI group significantly outweighed that in the PGT group, indicating that more embryos were available for further transfer. It has been reported that a proportion of the discarded embryos, due to poor morphological evaluation for blastocyst biopsy or cryopreservation, could also result in euploid newborns ( Lai et al , 2020 ). Further embryo loss during PGT process would further reduce the oocyte utilisation rate.…”
Section: Discussionmentioning
confidence: 99%
“…While existing guidelines and consensus ( Alpha Scientists in Reproductive Medicine and ESHRE Special Interest Group of Embryology, 2011 ) do not recommend discarding low-grade blastocysts ( De los Santos et al , 2016 ; Morbeck, 2017 ; Practice Committees of the American Society for Reproductive Medicine (ASRM) and the Society for Reproductive Biologists and Technologists (SRBT), 2022 ), some clinics across the world routinely discard low-grade blastocysts as a matter of policy ( Rubio et al , 2014 ; Comstock et al , 2015 ; Munch et al , 2015 ; Lai et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%